Kajian Kesesuaian Dan Daya Dukung Kawasan Wisata Di Pantai Penganak Kabupaten Bangka Barat - panji santoso; Sudirman adibrata; Fika Dewi Pratiwi (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2023)
Penganak Beach, which is located in Air Gantang Village, Parittiga District, West Bangka Regency. The magnitude of the tourism potential in Penganak Beach is expected to increase the number of tourist visits, but still provide aspects of security and comfort for tourists. The purpose of this research is to analyze the land suitability index for beach tourism in the recreation category and to analyze the carrying capacity of beach tourism areas in Penganak Beach. This research was conducted in October 2022 which took place at Penganak Beach, Air Gantang Village. Data collection was carried out by means of field observations using the purposive sampling method with analysis of the tourism suitability index and the carrying capacity of the area so that three stations were obtained. The results of the parameter measurement research carried out obtained the results of the tourism suitability index and the carrying capacity of the Penganak beach area, namely; The average of Station I is 76.45%, Station II is 81.08% and Station III is 78.97% for all stations on Penganak Beach with a tourism suitability index which is included in the S1 category (very suitable), while the area's carrying capacity is around 2,601 people/day and has not exceeded the carrying capacity of the region